Cytoid, colloid and large intra-blister round bodies and c-ANCAs in a case of erythema multiforme - Ana Maria Abreu Velez; Vickie M. Brown; Michael S. Howard (Our Dermatology Online, 2017)
Erythema multiforme is an acute, often self-limited and occasionally lethal syndrome with distinctive skin lesions and/or mucosal lesions; the disease has multiple triggers, including medications. We describe a 68 year old African American female on multiple medications; the patient suddenly presented with recurrent, flaccid bullae and erythematous circular lesions on her face, neck, genitals, hands and legs. Biopsies for hematoxylin and eosin (H&E) examination, direct immunofluorescence (DIF) and immunohistochemistry (IHC) stains were performed. The histology displayed erythema multiforme with epidermal blisters, defragmented melanocytes and other cell debris inside the blister. DIF revealed deposits of IgG, IgM, IgA, IgD, Complement/C3, C4, and fibrinogen within the epidermis; and around upper dermal vessels. Anti-neutrophil cytoplasmic antibodies (c-ANCAS) were present as part of "large round bodies" inside the blisters, and as part of both cytoid and colloid bodies. Staining for Von Willembrand factor, CD68, myeloperoxidase and CD45 was seen on cell fragments within the blisters, as well as within the inflammatory infiltrate in the dermis. In this case cystoid, colloid and "large round bodies" may represent amalgamations of multiple cell fragments, with immunoglobulins and complement. Overall, a strong immunologic response was observed with c-ANCAs, caused by multiple medications.